The Effect of Information Technology Perception and Risk Perception on Customer Interest in Using Mobile Banking with Trust as an Intervening Variable (Case Study at Bank BRI, Kupang City, East Nusa Tenggara) - Janri Manafe; Tuti Setyorini (Enrichment : Journal of Management, 2022)
This study aims to analyze the significance of the influence of Information Technology Perception on customer interest in using mobile banking at Bank BRI Kupang City, East Nusa Tenggara, which is mediated by trust and risk perception. The data collection method in this study was a questionnaire. The source of data for this study is primary data which is the answer to the questionnaire shared with respondents, and secondary data in the form of data on the number of customers who use mobile banking for more than 3 years at bank BRI Kupang City NTT. The population in this study is the number of BRI bank customers in Kupang City, East Nusa Tenggara, who use mobile banking. The samples taken were representatives of several people who used mobile banking with a period of more than three years, with the sampling technique being a purposive sampling technique, which is a sampling method based on certain criteria in accordance with the research objectives. Data analysis techniques use Structural Equation Modeling (SEM) analysis.